Carbonic anhydrase in the membrane of the endoplasmic reticulum of male rat liver. - Ono, Y (1992)
We have prepared subcellular fractions of male rat liver homogenate by the method of Lewis and Tata [Lewis, J. A. & Tata, J. R. (1973) J. Cell Sci. 23, 447-459], further purifying the membranes of the microsomal fraction by exposure to 0.01% Triton X-100 and centrifugation. We determined the purity of the fractions with marker enzymes and measured carbonic anhydrase (CA; EC 4.2.1.1) activity in intact and solubilized particulates with 18O exchange between CO2/HCO3- and water. We measured the concentration of CA by titration with a sulfonamide inhibitor, ethoxzolamide, obtaining an average value of 3.8 mumol/mg of microsomal membrane protein. The equilibrium constant for binding ethoxzolamide was 0.49 x 10(-9) M. The Km for CO2 was 1.7 mM and the turnover number was 560,000 sec-1, characterizing this as a membrane-bound, high-activity isozyme of type IV. By electron microscopy of tissue sections after staining with a cobalt precipitation technique, CA was seen in small cytoplasmic vesicles in hepatocytes and in microsomal particles and membranes. There was a sulfonamide-resistant (isozyme type III) and a sulfonamide-sensitive (isozyme type II) CA in the cytosol but none in the rapidly sedimenting endoplasmic reticulum. We conclude that there is no CA normally within the matrix of the cell endoplasmic reticulum but that the CA type III found in the microsome may have been captured from the cytosol during resealing. Thus the adult male rat hepatocyte contains CA type IV in the membrane of the endoplasmic reticulum and CA type II and CA type III in the cytoplasm.